2012
DOI: 10.22456/1982-8918.29764
|View full text |Cite
|
Sign up to set email alerts
|

As Configurações Do Futebol Brasileiro: Análise Da Trajetória De Um Treinador

Abstract: No presente artigo objetivou-se analisar a trajetória de um Treinador de futebol, levantando informações que possam auxiliar na discussão sobre formação e atuação profissional em Educação Física e Esportes. A pesquisa, de caráter qualitativo, utilizou História de Vida como método de coleta de dados. Para elucidar e articular questões abordadas utilizou-se conceitos da teoria sociológica de Norbert Elias. A partir da trajetória expressa e da proposta de configuração de Elias, concluímos que a figura do Treinado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 3 publications
0
3
0
3
Order By: Relevance
“…49,50 During their coaching phase, the coach developers upgraded their certifications and qualifications in an attempt to enhance their coaching skills, to address the legal needs in Brazil, 3 and to consolidate their professional identity as coaches. Brazilian studies involving sport coaches [51][52][53][54] have shown the main motivation for entering in physical education university programs is related to the need for professional certification. However, coaches usually keep seeking specific sport knowledge during this phase, as a result, the courses provided by sports organizations (associations and federations) are recognized as a central learning opportunity for them in formal contexts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…49,50 During their coaching phase, the coach developers upgraded their certifications and qualifications in an attempt to enhance their coaching skills, to address the legal needs in Brazil, 3 and to consolidate their professional identity as coaches. Brazilian studies involving sport coaches [51][52][53][54] have shown the main motivation for entering in physical education university programs is related to the need for professional certification. However, coaches usually keep seeking specific sport knowledge during this phase, as a result, the courses provided by sports organizations (associations and federations) are recognized as a central learning opportunity for them in formal contexts.…”
Section: Discussionmentioning
confidence: 99%
“…During this phase of the coach developers pathways, there seems to be a combining of the tacit knowledge constructed in the surfing context and the conceptual knowledge developed in formal opportunities of learning. 53,54 The reasons that the coaches became coach developers were associated with personal and social aspects: (a) The accumulation of surfing experience, (b) the professional certification and qualification acquired throughout the years, (c) the recognition of expertise by colleagues, and (d) the need to align surf coaching with the Physical Education professional domain. Subsequently, the coaches' consolidation of knowledge and competences, and the establishment of sports organizations (ACES and IBRASURF) characterized the transition phase to coach developers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…É necessário para o treinador possuir conhecimentos e experiências que ultrapassem as vivências de ex-atleta. Para isso o treinador precisa acompanhar a evolução dos conhecimentos científicos aplicados ao contexto esportivo (10,26). Ramos et al 5 Sobre as condições laborais que os treinadores de basquetebol têm à disposição, a falta de dedicação exclusiva ao cargo de treinador foi um dos fatores citados pelos entrevistados que mais prejudica seu trabalho.…”
Section: Discussionunclassified
“…Depois, as entrevistas com os treinadores foram divididas em pequenos trechos, denominadas miniunidades (MU´s). Elas são consideradas as menores partes compreensíveis de um texto que expressam uma ideia ou informação (25)(26). A partir das MU´s foi possível analisar as falas dos entrevistados dentro de temáticas específicas (25)…”
Section: Análise Dos Dadosunclassified